2008
DOI: 10.1038/ng.170
|View full text |Cite
|
Sign up to set email alerts
|

Age-related macular degeneration is associated with an unstable ARMS2 (LOC387715) mRNA

Abstract: Age-related macular degeneration (AMD) is a prevalent multifactorial disorder of the central retina. Genetic variants at two chromosomal loci, 1q31 and 10q26, confer major disease risks, together accounting for more than 50% of AMD pathology. Signals at 10q26 center over two nearby genes, ARMS2 (age-related maculopathy susceptibility 2, also known as LOC387715) and HTRA1 (high-temperature requirement factor A1), suggesting two equally probable candidates. Here we show that a deletion-insertion polymorphism in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
306
3
5

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 370 publications
(348 citation statements)
references
References 27 publications
23
306
3
5
Order By: Relevance
“…We attempted to confirm the SNP associations in or near HLA-DQB1 using HapMap imputed discovery sample results available in the large (n477 000) AMD Gene Consortium GWAS meta-analysis (http://www.sph.umich.edu/csg/abecasis/public/amdgene2012/), 16 but neither rs9274390 nor SNPs in moderate-to-high LD with our top association were included in that analysis, likely due to insufficient coverage in HapMap in the region. Although our analysis included 5640 SNPs (2116 SNPs were directly genotyped) within ± 250 000 base pairs around rs9274390, 166 SNPs were found in the Consortium meta-analysis results.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We attempted to confirm the SNP associations in or near HLA-DQB1 using HapMap imputed discovery sample results available in the large (n477 000) AMD Gene Consortium GWAS meta-analysis (http://www.sph.umich.edu/csg/abecasis/public/amdgene2012/), 16 but neither rs9274390 nor SNPs in moderate-to-high LD with our top association were included in that analysis, likely due to insufficient coverage in HapMap in the region. Although our analysis included 5640 SNPs (2116 SNPs were directly genotyped) within ± 250 000 base pairs around rs9274390, 166 SNPs were found in the Consortium meta-analysis results.…”
Section: Resultsmentioning
confidence: 99%
“…Although a few small candidate gene studies found that certain HLA class I and class II polymorphisms were associated with a predisposition to AMD, 14,15 the largest genome-wide association study (GWAS) meta-analysis conducted by the AMD Gene Consortium, which included more than 77 000 subjects, did not identify any HLA polymorphisms that were independently associated with the risk of AMD. 16 The AMD Consortium meta-analysis, although well powered to detect common variants of small effect, included a number of studies that utilized genotyping arrays, with array density ranging from 165 770 to 668 238 genotyped SNPs after QC, with incomplete coverage of genetic variants in the HLA region. In addition, imputation was conducted using the HapMap reference panel, which does not include the majority of known HLA variants, limiting the ability of the individual studies to infer HLA genotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Although the precise role of ARMS2 in AMD disease aetiology has yet to be elucidated, its role in mitochondrial function is thought to be important (Rivera et al, 2005). Recently, it has been demonstrated that the normal protein coded for by ARMS2 is associated with mitochondria, and they were able to localize this protein product to the ellipsoid region of the photoreceptors, which are known to be rich in mitochondria (Fritsche et al, 2008;Hoang et al, 2002). It has therefore been postulated that the role of ARMS2 in AMD pathogenesis relates to mitochondrial function and/or its involvement in cell turnover and/or the removal of cellular debris from the photoreceptor-RPE complex.…”
Section: Discussionmentioning
confidence: 99%
“…4,6 Common single nucleotide polymorphisms (SNPs) in the complement factor H (CFH) gene on chromosome 1, [7][8][9][10] and in two loci on chromosome 10q26, that is, ARMS2 (formerly labelled as LOC387715) [11][12][13][14][15] and the HtrA serinepeptidase 1 (HtrA1) gene [16][17][18][19] showed strong associations with the risk of advanced AMD. These results have been extensively replicated in studies conducted in various populations and settings (for an overview, see Jakobsdottir et al 20 ).…”
Section: Introductionmentioning
confidence: 99%